Total factor productivity in food industries of Iran - Ahmad Afrooz,; Abdul Rahim, Khalid; Mohd Noor, Zaleha; Lee, Chin (Canadian Center of Science and Education, 2011)
Considering to Importance of Food Industries ( Priority of the Non-oil Exports in Foreign Trade, respond to Nutrition of population and Prevention of Wastage) This paper examine the levels of labor, total productivity and technical changes in food industries and compare with total industries of Iran over the 1971-2006 period. The results show that labor productivity and total factor productivity in food industries were lower than average total industries over the period. Also the estimation of technical changes show that measure of technical change in food industries was 0.09 percent while for total industries was 0.16 percent over the period.